Crop Variety Improvement and Its Effect on Productivity: The Impact of International Agricultural Research 2003
DOI: 10.1079/9780851995496.0361
|View full text |Cite
|
Sign up to set email alerts
|

The impact of investments in agricultural research on total factor productivity in China.

Abstract: This chapter presents a framework for studying the effect of national and international investments (which include the flow of germplasm between the international agricultural research centres and China's national agricultural research system) on research and extension in China, focusing on rice, wheat and maize, and discusses the impact of such investments on the development of productivity-increasing technology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
4
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 0 publications
1
4
0
Order By: Relevance
“…In China, after a rapid increase from 4.5 t/ha in 1959 to 6.6 t/ha in 1981, experimental yield increased little in the 1980s and 1990s ranging from 6.5 t/ha to 6.8 t/ha. Similar to these trends, Rozelle et al (2003) found that the TFP for rice increased little from the mid‐1980s to the mid‐1990s.…”
Section: Research Benefits and Contribution Of International Researchsupporting
confidence: 57%
“…In China, after a rapid increase from 4.5 t/ha in 1959 to 6.6 t/ha in 1981, experimental yield increased little in the 1980s and 1990s ranging from 6.5 t/ha to 6.8 t/ha. Similar to these trends, Rozelle et al (2003) found that the TFP for rice increased little from the mid‐1980s to the mid‐1990s.…”
Section: Research Benefits and Contribution Of International Researchsupporting
confidence: 57%
“…One of the most important capital inflows which helps alleviate poverty in developing countries is foreign aid [55][56][57]. The effects of foreign aid range from poverty alleviation and combating food insecurity to a broader spectrum of issues, including strengthening domestic food production, the establishment of agriculture institutes, and the promotion of agriculture development [58][59][60]. Both the World Bank and the OECD strongly focus on the role of aids in support of agriculture development and poverty reduction in developing countries [61,62].…”
Section: Selection Of Variablesmentioning
confidence: 99%
“…From an initial focus on building agricultural institutions, increasing food production and promoting agricultural growth, aid has tended to re‐focus on a wider range of second generation problems such as policy reforms for more open, liberal economies (Herdt, ). Agricultural research investment contributed immensely to China's agricultural productivity growth over the past 40 years (Fan et al ., ; Rozelle et al ., ) and also in India (Janaiah et al ., ). Rates of return on agricultural research investment are found to be close to or above 50% (World Bank Operations Evaluation Department, , ; Anderson and Feder, ; Fan et al ., , ; Fan and Pardey, ; Fan and Rao, ; Lipton, ).…”
Section: Introductionmentioning
confidence: 98%